2007
DOI: 10.2174/092986707782793880
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphin Analogs

Abstract: Opiate alkaloids, such as morphine, are powerful analgesic agents that are the drugs of choice for the treatment of severe pain. The pharmacological effects of opiates are mediated through the binding and activation of membrane-bound opioid receptors that are found in the central and peripheral nervous systems. Opioid receptors have been classified into three different types, mu, delta and kappa, and are activated by the specific ligands. It has been demonstrated that the most potent antinociceptive effects ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 79 publications
(107 reference statements)
0
31
0
1
Order By: Relevance
“…These unfavorable pharmacological properties have hindered the development of EMs for clinical use. To overcome the limited access of exogenously administered EMs to the brain and to search for analogs with minimal side-effects, numerous chemical modifications of their structure have been proposed [30][31][32][33].…”
Section: Pharmacology Of Opioid Receptor Typesmentioning
confidence: 99%
“…These unfavorable pharmacological properties have hindered the development of EMs for clinical use. To overcome the limited access of exogenously administered EMs to the brain and to search for analogs with minimal side-effects, numerous chemical modifications of their structure have been proposed [30][31][32][33].…”
Section: Pharmacology Of Opioid Receptor Typesmentioning
confidence: 99%
“…In efforts to develop new candidate drugs with antinociceptive activity, numerous chemical modifications have been performed to improve the pharmacological profile of endomorphins (2). Proline in position 2 of endomorphins is a spacer residue (3), connecting two pharmacophoric aromatic residues, Tyr 1 and Trp/Phe 3 .…”
Section: Opioid Receptor Binding Assays Of Endomorphin‐2 Analogsabmentioning
confidence: 99%
“…Moreover, the amino acid, Phe 4 , is free to adopt a bioactive conformation that is independent of the other amino acids [11]. These results further point out the importance of the orientation of the C-terminal aromatic side chain for binding affinity to the MOR, indicating different structural features for each residues would influence the SARs and further affect the affinity and selectivity to MOR strongly [12].…”
Section: Introductionmentioning
confidence: 70%
“…As for conformational properties on modifications at C-terminus, a series of hydrophobic non-aromatic residues for Phe 4 by substitution of the C-terminal amide group has been studied [10]. Furthermore, it has been found that the (R) chiral center of the fourth amino acid may induce a proper spatial arrangement of the third aromatic ring of endomorphin analogues [12]. Hence, not only pharmacophoric residues, but also the Cterminal residue plays a critical role in the biological activity of the endomorphins.…”
Section: Introductionmentioning
confidence: 99%